Стреляй первым: [роман, повесть] / Сергей Гайдуков - Гайдуков Сергей Викторович (Серия "Чёрная кошка", 1997)
Экземпляры: Аб (20141030) / Инвентарный номер: 101721 / Цена: 40.00 / Авт.знак: Г 14 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6